Analisis Mengenai Problematika yang Dihadapi Karyawan Wanita di Bidang Perhotelan - Maria Pia Adiati (Bina Nusantara University, 2013)
Nowadays it is seen that women work in every line of work. This is also clearly seen in tourism industry and particularly in hotel industry. Many positions in hotel are held by women. These women have big participation in running the hotel industry while they have another task as a housewife while working. It is interested to analyze the problems faced by the women who work in the hotel since it relates to the nature of woman such has pregnant, to give birth, and to breast-feed the baby. The nature of woman must not be forgotten eventhough she is working and the hotel management should give attention to this nature since it relates to the daily hotel operational where the woman employee is involved in it.